Czech and Czechoslovak Autoklub during the Period 1904-1928 - Marek Waic (Jan Długosz University in Częstochowa, 2019)
The article looks into motor racing and the activities of the Czech and Czechoslovak Autoclub since its establishment in 1904 until 1928. The activity of the Autoklub is analyzed mainly in connection with the establishment and activities of the social elites in interwar Czechoslovakia. Thanks to its representatives' contacts with leading politicians and industrialists in the country, the Autoklub of the Czechoslovak Republic was a very influential organization. In its activities, it benefited from economic stabilization and the subsequent economic boom in the first decade of the existence of interwar Czechoslovakia